1998
DOI: 10.1267/ahc.31.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Extracellular Matrix on the Lipogenesis of Cultured White Fat Cells.

Abstract: Collagenase digests from subcutaneous fat tissue of new born rats were cultured on different types of collagen gel containing 50% type I collagen, on fibronectin (Fn) or on laminin (Lm). On day 6, 17% of cells on a plastic substratum differentiated and had multilocular or unilocular cytoplasmic lipid droplets (CLDs). Cells on each type of collagen and on Lm had more CLDs than those on a plastic substratum.The extent of lipogenesis showed the following decreasing order: cells on Lm (80%), on type IV + I collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…The collagen gel cultures exhibited higher GPDH activity, leptin synthesis, and TG accumulation on a per cell basis but achieved lower cell densities. A similar result was reported by Yonemitsu et al (49), who use a "ceiling culture" system to show that stromal cells isolated from subcutaneous fat of newborn rats differentiated to a significantly greater extent on type I collagen gel compared with TCP. One possible explanation for this phenomenon involves biophysical stimulation of mitogenic signaling pathways.…”
Section: Discussionsupporting
confidence: 84%
“…The collagen gel cultures exhibited higher GPDH activity, leptin synthesis, and TG accumulation on a per cell basis but achieved lower cell densities. A similar result was reported by Yonemitsu et al (49), who use a "ceiling culture" system to show that stromal cells isolated from subcutaneous fat of newborn rats differentiated to a significantly greater extent on type I collagen gel compared with TCP. One possible explanation for this phenomenon involves biophysical stimulation of mitogenic signaling pathways.…”
Section: Discussionsupporting
confidence: 84%
“…The reduction of TG accumulation levels in the presence of EDHB indicates that adipocytes require collagens in the surrounding environment during differentiation. Subjecting adipocytes to ECM components demonstrates their influence, which is often negative with fibronectin and promotive with basement membrane relatives on adipose conversion (Spiegelman and Ginty, 1983; Rodriguez Fernandez and Ben‐Ze'ev, 1989; Hausman et al, 1996; Yonemitsu et al, 1998). We found that collagen types V and VI were the only collagens to improve the reduced TG content caused by EDHB, while the inhibitory effect remained impaired for cells seeded on the other type of collagen substrata.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of DAB and H2O2 used in the present study were higher than those used in recent immunohistochemical studies [6,20], because immunostaining intensity does not reflect the activity of labeled enzyme and gives underestimated results when the chromogen and/or substrate concentration is low [4,10,16]. Thus, the possibility that the disproportionate relationship between the intensity and antigen in sections relates to low concentrations of the chromogen and the substrate may be ruled out in the present study.…”
Section: Discussionmentioning
confidence: 55%